Hubungan Harga Diri dengan Presentasi Diri Remaja Pengguna Instagram - Akbar Reza; Basti Tetteng (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Adolescence is an important developmental phase for individuals. During this phase, teenagers require direct interaction with their environment. However, faceto-face interactions have decreased due to the rise of social media. One of the social media platforms that can be used is Instagram. Instagram offers engaging features such as photo and video sharing, allowing teenagers to express themselves. The process through which teenagers express themselves on social media is called selfpresentation. Teenagers’ self-presentation can be positive, authentic, or negative, inauthentic, and is influenced by their self-esteem. Therefore, this study aims to explore the relationship between self-esteem and self-presentation among Instagram users. This research employs a quantitative method with 337 adolescent Instagram users as respondents. The analysis technique used is multiple correlation testing. The findings indicate a positive relationship between self-esteem and selfpresentation among Instagram users, with the relationship between self-esteem and real self-presentation showing the strongest contribution, with a correlation coefficient of 0.573. This suggests that the higher the self-esteem, the more positive the self-presentation by the teenage Instagram users. The implications of this study are that teenagers' self-esteem can enhance their self-presentation in a positive way, aligned with their true selves.